KOMPARASI KUALITAS FLOWING CONCRETE DITINJAU DARI TINGGI JATUH PENGECORAN DAN JENIS SEMEN - Eko Raharjo, Nuryadin (Universitas Negeri Yogyakarta, 2006)
ABSTRACTPumping method is the most frequently used to transport concrete verticallyin multistory building construction. However, such pumping method is still upagainst many problems: (1) the high performance of concrete requires a highquality of flowing concrete; (2) close-meshed framing causes difficulties indistributing the concrete. This research aims to clarify the influence of foundryfall height and cement type toward compressive strength and water absorptiondifference of flowing concrete.Two type of cements, Portland Cement (PC) and Portland PozzolandCement (PPC), were tested in this experimental research. Variation of foundryfall height is categorized into Oem, 35cm, 70cm, and 100cm. Compressivestrength and water absorption of each variant of flowing concrete was measuredafter reaches age of 90 days; three of test objects represent by one data.The research concludes that: (1) there is a compressive strength differenceof flowing concrete using both PC and PPC as the result of foundry fall height.Maximal compressive strength difference is reached at fall height of 100cm; forPC is 15.36% and PPC is 6.690/0. (2) there is a water absorption difference offlowing concrete as the result of foundry fall height using both PC and PPC.Maximal water absorption difference is reached at fall height of 100cm; for PCis 12.05% and PPC is 32.50%.Keywords: fall height, flowing concrete, compressive strength, water absorption,cement type